IL1B and DEFB1 Polymorphisms Increase Susceptibility to Invasive Mold Infection After Solid-Organ Transplantation. (14th November 2014) - Wójtowicz, Agnieszka; Gresnigt, Mark S.; Lecompte, Thanh; Bibert, Stephanie; Manuel, Oriol; Joosten, Leo A.B.; Rüeger, Sina; Berger, Christoph; Boggian, Katia; Cusini, Alexia; Garzoni, Christian; Hirsch, Hans H.; et al.
Abstract: Background.  Single-nucleotide polymorphisms (SNPs) in immune genes have been associated with susceptibility to invasive mold infection (IMI) among hematopoietic stem cell but not solid-organ transplant (SOT) recipients. Methods.  Twenty-four SNPs from systematically selected genes were genotyped among 1101 SOT recipients (715 kidney transplant recipients, 190 liver transplant recipients, 102 lung transplant recipients, 79 heart transplant recipients, and 15 recipients of other transplants) from the Swiss Transplant Cohort Study. Association between SNPs and the end point were assessed by log-rank test and Cox regression models. Cytokine production upon Aspergillus stimulation was measured by enzyme-linked immunosorbent assay in peripheral blood mononuclear cells (PBMCs) from healthy volunteers and correlated with relevant genotypes. Results.  Mold colonization (n = 45) and proven/probable IMI (n = 26) were associated with polymorphisms in the genes encoding interleukin 1β (IL1B; rs16944 ; recessive mode, P = .001 for colonization and P = .00005 for IMI, by the log-rank test), interleukin 1 receptor antagonist ( IL1RN ; rs419598 ; P = .01 and P = .02, respectively), and β-defensin 1 ( DEFB1 ; rs1800972 ; P = .001 and P = .0002, respectively). The associations with IL1B and DEFB1 remained significant in a multivariate regression model ( P = .002 for IL1B rs16944 ; P = .01 for DEFB1 rs1800972 ). The presence of 2 copies of the rare allele of rs16944 or rs419598 was associated with reduced Aspergillus -induced interleukin 1β and tumor necrosis factor α secretion by PBMCs. Conclusions.  Functional polymorphisms in IL1B and DEFB1 influence susceptibility to mold infection in SOT recipients. This observation may contribute to individual risk stratification.